Big city life: carnivores in urban environments - Bateman, Bill; Fleming, P. (Wiley-Blackwell Publishing Ltd., 2012)
Cities may represent one of the most challenging environments for carnivorous mammals. For example, cities have a dearth of vegetation and other natural resources, coupled with increased habitat fragmentation and an abundance of roads as well as altered climate (e.g. temperature, light, rainfall and water runoff). It is therefore intriguing that several carnivore species have become established in cities across the globe. Medium-sized carnivores such as the red fox, coyote, Eurasian badger and raccoon not only survive in cities but also have managed to exploit anthropogenic food sources and shelter to their significant advantage, achieving higher population densities than are found under natural conditions. In addition, although they may not live permanently within cities, even large carnivores such as bears, wolves and hyaenas derive significant benefit from living adjacent to urbanized areas. In this review, we examine the history of urban adaptation by mammalian carnivores, explore where they are living, what they eat, what kills them and the behavioural consequences of living in urban areas. We review the biology of urban carnivores, exploring traits such as body size and dietary flexibility. Finally, we consider the consequences of having populations of carnivores in urbanized areas, both for humans and for these charismatic mammals. In conclusion, in a time of massive environmental change across the globe, the continuing encroachment of urbanization upon wilderness areas is substantially reducing the availability of natural habitats for many species; therefore, understanding the biology of any taxon that is able to adapt to and exploit anthropogenically disturbed systems must aid us in both controlling and developing suitable conservation measures for the future of such species.